1992
DOI: 10.1302/0301-620x.74b3.1587888
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of the meniscus in anterior cruciate insufficiency. Arthroscopic analysis

Abstract: We studied arthroscopically the meniscal pathology in 100 patients with functional instabffity of the knee from isolated rupture of the anterior cruciate ligament at an average time of three years after injury. Meniscal tears were observed in 86 patients and multiple lesions of both menisci were common. An incomplete longitudinal cleavage, visible on both surfaces of the posterior horn, was seen in more than half the knees and seemed to indicate progressive meniscal deterioration. Clinical examination was unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 0 publications
1
51
0
2
Order By: Relevance
“…This high prevalence makes it impossible to determine the combined versus the individual effects of ACL tears and meniscal tears on OA outcomes. Indeed, many of these meniscal tears probably occurred months to years after the original ACL injury (27,28). We have also previously reported that in this sample, meniscal tears have no association with OA pain severity (29).…”
Section: Discussionmentioning
confidence: 53%
“…This high prevalence makes it impossible to determine the combined versus the individual effects of ACL tears and meniscal tears on OA outcomes. Indeed, many of these meniscal tears probably occurred months to years after the original ACL injury (27,28). We have also previously reported that in this sample, meniscal tears have no association with OA pain severity (29).…”
Section: Discussionmentioning
confidence: 53%
“…The injury mechanism is unclear: it would appear that knees in which the AHMM is not directly attached to the tibia [8] are predisposed to this type of meniscal injury. The instability caused by tearing of the ACL may also contribute to this injury, through a mechanism similar to that reported by Finsterbush [3] and Irvine [6]. This paper reports on two cases of injury-induced detachment of the AHMM in knees with a torn ACL.…”
Section: Introductionsupporting
confidence: 58%
“…In a series of 98 knees with chronic ACL damage, Finsterbush [3] observed 14 cases of loosening and subluxation of the AHMM. Irvine [6] maintains that in unstable knees meniscal tears extend anteriorly. In the second case reported here, the initial injury may have been a bucket-handle tear of the anterior portion of the MM; following rupture of the posterior portion of the handle, an anterior flap would be left locked in the intercondylar notch.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ACL injury can often be debilitating and result in long-term functional impairment including knee instability [5] and changes in motor unit recruitment during low-level contractions [6]. Subsequently, this often causes further damage of the menisci and articular surfaces which reduces knee function and in turn reduces a patient's level of physical activity [7,8].…”
Section: Introductionmentioning
confidence: 99%